The Effect Of Knowledge Sharing And Organizational Support On Organizational Citizenship Behavior (OCB) Among Employees At The Food Security Agency Of North Bengkulu Regency - Mustika Zulfa Berliani; Sri Ekowati (Jurnal Fokus Manajemen, 2026)
This study aims to determine the influence of Knowledge Sharing and Organizational Support on Organizational Citizenship Behavior (OCB) among employees of the Food Security Office of North Bengkulu Regency, both partially and simultaneously. The object of this research is all employees of the Food Security Office of North Bengkulu Regency totaling 41 people. The data collection methods used in this study were observation and the distribution of questionnaires to respondents. The data analysis techniques used include instrument testing, respondent response analysis, classical assumption testing, multiple linear regression analysis, coefficient of determination (R²), and hypothesis testing.The results show that Knowledge Sharing has a positive and significant effect on Organizational Citizenship Behavior (OCB) among employees of the Food Security Office of North Bengkulu Regency. In addition, Organizational Support also has a positive and significant influence on Organizational Citizenship Behavior (OCB) among employees of the Food Security Office of North Bengkulu Regency. Therefore, it can be concluded that Knowledge Sharing and Organizational Support partially and simultaneously influence Organizational Citizenship Behavior (OCB) among employees of the Food Security Office of North Bengkulu Regency.